2019
DOI: 10.3390/nano9091290
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Mechanisms of Insensitive Explosive FOX-7 and Graphene Oxides from Ab Initio Calculations

Abstract: Energetic material–graphene oxide (EM–GO) composites exhibit excellent thermal stability and insensitivity to mechanical stimuli. The interfacial interactions play an important role in affecting the structural and electrical properties of EM–GO composites. FOX-7 crystal with a wave-shaped layer structure is an ideal prototype system for matching with oxygen-rich GO monolayers to form FOX-7–GO composites. Here, we conducted a systematic investigation on FOX-7–GO composites by dispersion-corrected density functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Li et al used a prolonged high-power laser (8 W, 500 ms, 1064 nm) to initiate CL-20 powder, but it basically only burned at the irradiation point and could not keep burning. It is reported in several studies that CL-20-based thin films, doped with GO, which has a high photothermal conversion efficiency as well as nano-Al, , could be initiated by laser. Since laser detonation is safer and more reliable than other traditional detonation methods, it is of great research value to study the laser potential initiation ability of the CL-20 composite to possibly replace lead azide.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al used a prolonged high-power laser (8 W, 500 ms, 1064 nm) to initiate CL-20 powder, but it basically only burned at the irradiation point and could not keep burning. It is reported in several studies that CL-20-based thin films, doped with GO, which has a high photothermal conversion efficiency as well as nano-Al, , could be initiated by laser. Since laser detonation is safer and more reliable than other traditional detonation methods, it is of great research value to study the laser potential initiation ability of the CL-20 composite to possibly replace lead azide.…”
Section: Introductionmentioning
confidence: 99%
“…Two years later, FOX-7, RDX, and HMX are also modeled between graphene layers to investigate two-dimensional confinement [18] , it was found that FOX-7, which is a flat molecule, was more stabilized in graphene than in CNTs, while RDX and HMX were more stable in CNTs due to their nonplanar shapes. In 2019, a systematic investigation on FOX-7/GO interfacial interactions by dispersion-corrected density functional approach were conducted [26] , it was revealed that the synergistic effect of interfacial charge transfer and hydrogen bonding make FOX-7/GO exhibit excellent thermal stability, the hydrogen bonds could break or form at interfaces, which helps the coating GO sheets to FOX-7 surface and dissipates the mechanical stimuli energy.…”
Section: Composite Of Graphene and Emsmentioning
confidence: 99%
“…GO can be combined with ATRZ as a desensitizer candidate. The interaction interface of FOX-7-GO mixture composites [13] , which is an ideal prototype system, were studied by dispersion-corrected density functional approach. The results revealed that the interfacial charge transfer from FOX-7 to GO and hydrogen bonds are two important issues, leading to relatively strong interaction between FOX-7 and GO.…”
Section: Introductionmentioning
confidence: 99%